Ficus septica Burm.f. Leaves Ethanolic Extract Triggered Apoptosis on 7,12-Dimethylbenz[a]anthracene-Induced Rat Mammary Carcinogenesis Qualitatively - Anindyajati, .; Darma, Andita Pra; Nurzijah, Ika; Septhea, Dita Brenna; Nugroho, Agung Endro (Indonesian Journal of Cancer Chemoprevention, 2012)
Ficus septica Burm.f.ethanolic extract (FEE) shows cytotoxic effects on several cancer cell lines. Our research aimed to investigate the effect of FEE on apoptosis induction and p53 expression against carcinogenesis of 7,12-Dimenthylbenz[a]anthracene (DMBA)-induced rat mammary. The research was conducted by comparing both apoptosis induction and p53 expression in DMBA-induced rats that were treated with FEE against control groups. Cells that undergo apoptosis were visualized by Double Staining method with acridine orange and ethidium bromide, while p53 expression was detected by IHC staining. Double staining result showed increased occurrence of apoptotic cells compared to the control groups. IHC staining pf P53 did not show significant difference between treatment and control groups. However, FEE was able to repair morphology of cells undergoing carciogenesis. Thus, we conclude that FEE has an anti carciogenic activity on DMBA-induced rat mammary through apoptosis induction without affecting p53 expression. Therefore, the ethanolic extract of Ficus septica leaves is a potential chemo-preventive agent on breast cancer. Further study on its molecular mechanism needs to be exploredKeywords: Ficus septica, breast cancer, 7,12-Dimethylbenz[a]anthracene, carciogenesis, apoptosis, p53